Effects of thickness and hydrophobicity of double microporous layer on the performance in proton exchange membrane fuel cells. Issue 18 (7th December 2020) - Lin, Guangyi; Liu, Shouyi; Qu, Siyuan; Qu, Guangkai; Li, Tianya; Liang, Zhenning; Hu, Yafei; Liu, Fumin
Abstract: In this paper, a multi‐layer gas diffusion layer (GDL) is designed. The GDL consists of a single carbon paper backing layer and dual microporous layers (MPLs). Moreover, the effects of thickness and hydrophobicity of double MPL on the performance of proton exchange membrane fuel cells are investigated. From the test results of the water contact angle, conductivity, pore size distribution, and the polarization curve, it is found that the thickness adjustment increases the number of 0.5 to 7 μm and 20 to 100 μm pores in GDL, which is more conducive to water discharge. Therefore, the thickness adjustment is more favorable to the cell performance under high humidity. While the gradient hydrophobic design makes the MPL of the modified intermediate layer have a certain water‐retaining capacity to humidify the reaction gas, which has better effect under low humidity. At last, the results show that the optimized GDL meets a limit power density of 1.772 W/cm 2 under 60% humidification and 1.600 W/cm 2 under 100% humidification. Abstract : A multi‐layer GDL including a single carbon paper backing layer and dual MPLs was prepared, and the thickness and hydrophobicity of double MPL were optimized. The thickness adjustment was more conducive to the cell performance under high humidity by affecting pore size distribution, while the gradient hydrophobic design had better effect under low humidity by humidifying reaction gas.